2021
DOI: 10.2217/bmm-2020-0785
|View full text |Cite
|
Sign up to set email alerts
|

Breast Invasive Ductal Carcinoma Diagnosis with A Three-Mirna Panel in Serum

Abstract: Aim: Breast cancer, especially invasive ductal carcinoma (IDC), is the cause of a great clinical burden. miRNA could be considered as a noninvasive biomarkers for IDC diagnosis. Materials & methods: Two hundred and sixty participants (135 IDC patients and 125 healthy controls) were enrolled in a three-cohort study. The expression of 28 miRNAs in serum were detected with quantitative reverse transcription-PCR. Bioinformatic analysis was used for predicting the target genes of three selected miRNAs. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…Typical miRNAs, which are highly correlated with cancer based on the KEGG pathway analysis, were identified based on the human miRNA database ( Figure S4 ). KEGG enrichment analysis revealed that many of these down-regulation miRNAs including miR-125a-5p [ 53 , 54 ], miR-34a-5p [ 55 ], miR-132-3p [ 56 ], and miR-148b-3p, were BC biomarkers highly correlated with PEG-ReS2-based PTT. In addition, we found 37 up-regulation miRNAs ( Figure 6 e and Figure S5 ), including miR-133a-3p [ 57 , 58 ], miR-200c-5p, miR-9-3p, and miR-150-3p, which were also highly correlated with PEG-ReS 2 -based PTT.…”
Section: Resultsmentioning
confidence: 99%
“…Chen and Li established a serum three-miRNA panel (AUC = 0.880) that enhances the diagnostic e cacy of breast invasive ductal carcinoma. Therefore, the serum three-miRNA panel, including miR-9-5p, miR-34b-3p, and miR-146a-5p, holds tremendous potential as non-invasive biomarkers for diagnosing breast invasive ductal carcinoma [40] .…”
Section: Discussionmentioning
confidence: 99%